2015
DOI: 10.1098/rspa.2014.0662
|View full text |Cite
|
Sign up to set email alerts
|

Walking on a moving surface: energy-optimal walking motions on a shaky bridge and a shaking treadmill can reduce energy costs below normal

Abstract: Understanding how humans walk on a surface that can move might provide insights into, for instance, whether walking humans prioritize energy use or stability. Here, motivated by the famous human-driven oscillations observed in the London Millennium Bridge, we introduce a minimal mathematical model of a biped, walking on a platform (bridge or treadmill) capable of lateral movement. This biped model consists of a pointmass upper body with legs that can exert force and perform mechanical work on the upper body. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…In a previous study, we had argued that humans could reduce their walking metabolic cost by optimally walking on a shaking bridge [10]. That model ignored stability considerations.…”
Section: (F ) Energy Cost Increases When the Bridge Shakesmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study, we had argued that humans could reduce their walking metabolic cost by optimally walking on a shaking bridge [10]. That model ignored stability considerations.…”
Section: (F ) Energy Cost Increases When the Bridge Shakesmentioning
confidence: 99%
“…Estimating the metabolic cost for gaits observed in this current study, we find that the metabolic cost is lowest when the biped walks on solid ground and increases when the bridge starts shaking (figure 2e). We hypothesize that the short-timescale response of the humans will be governed by the constraint that they should not fall (thus increasing the cost), but if the subjects continued to walk on shaky bridges, they may learn to walk energy-efficiently [10], modifying their controller to be simultaneously energy-efficient and stable, perhaps using optimal feedback control [13].…”
Section: (F ) Energy Cost Increases When the Bridge Shakesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies have demonstrated that MEE during walking can be predicted using joint-space kinematic and kinetic data [41,42]. However, due to the lack of an accurate MEE model in joint space, incomplete proxies for MEE, such as center-of-mass work [43,44], segmental work [43,45], modified total mechanical work [45], rate of normalized absolute joint moment impulses [43], mechanical work derived from experimental efficiencies [46,47], and other combinations [48], are often used as approximations in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that the metabolic cost of walking can be reduced by providing an M–L restorative force acting on the subject’s pelvis [1921]. As well, modelling work has also shown that walking economy can be improved by having the walking surface oscillate and do work on the walking model [22]. Since the carried mass in our M–L load carriage device was oscillating out-of-phase, the M–L interaction force component was also out-of-phase, resembling a restorative force to the centreline similar to studies with elastically tethered subjects [1921].…”
Section: Introductionmentioning
confidence: 99%